ڕولێ روسیا د رێکەفتنا سایکس ـ پیکو دا 3/1/1916 - 7/11/1917 - صادق, محمد صالح ته‌یب (Sulaimani Journal for Humanities, 2018)
Abstract Many of non-specialists think that Sykes Picot was only a secret agreement between England and France in order to divide Ottoman state properties including Turkey, the Eastern Arabia, Armenia and Kurdistan, which was under Ottomans authority at that time. After the First World War in 1918 and according to Sykes Picot agreement, these two states divided Ottoman state properties between themselves with the exception of the present Turkey with some changes. One of these changes was when France waived Mosul province (southern Kurdistan) for England. This study tries to shed light on the role of Russia as a basic part to confirm that secret agreement. The three states (England, France and Russia) agreed that after achieving the victory on the Axis Powers (Germany, Austria empire , Hungary and Ottoman state), they would attach Bosporus strait, Istanbul city and Dardanelles strait under Russia's authority as well as northern Kurdistan including Zakho areas and Mateen mountains, in addition to eastern Kurdistan and Armenia. Russia was deprived from the post war spoils because of October Uprising in November 7, 1917 and the withdrawal of Russia from the war besides signing a peace treaty with Germany in 1918. Later, the revolutionary authorities in Russia announced all the secret agreements adopted by the Caesarean Russia with other governments including Sykes Picot. Eventually, they asked the nations of the world to stand against them and not to trust colonial states in the future.